Effect of metals on Daphnia magna and cladocerans representatives of the Argentinean Fluvial Littoral - Regaldo, Luciana María; Reno, Ulises; Gervasio, Susana Graciela; Troiani, Horacio Esteban; Gagneten, Ana María (Triveni Enterprises, 2014)
Fil: Regaldo, Luciana María. Universidad Nacional del Litoral. Facultad de Humanidades y Ciencias; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina